Polymerization of polypyrrole nanospheres on carbon nanotubes with PMo12-xWx as oxidant and redox dopant for supercapacitor. (9th September 2020) - Cao, Aiping; Li, Yafei; Chen, Zhongxing; Wang, Yanmin; Li, Tingxi; Han, Yongqin
Abstract: Polypyrrole (PPy) nanospheres are successfully assembled on the surface of multiwalled carbon nanotubes (MWNTs) with the aid of PMo12-x Wx (mixture of phosphomolybdic acid andphosphotungstic acid with molar ratio of 3:1) as both oxidant and the redox dopant. The resulting multi-walled carbon nanotubes (MWNTs)/PPy nanocomposites (MPNs) exhibited a well-defined core-shell structure, leading to the fast and efficient transmission/transfer of both electrolyte ions and electrons. An intrinsic increase in electrochemical performance of the nanocomposites has been achieved by the combination of the double-layer and the Faradaic capacitance originated from both PPy and PMo12-x Wx . In a typical three-electrode system, MPN10 (the mass ratio of MWNT: pyrrole is 10:90) can provide the highest specific capacitance of 570F/g. Moreover, in a typical two-electrode symmetric system with MPN10 as electrodes and polyvinyl alcohol (PVA)-H2 SO4 gel as electrolyte, the supercapacitor device exhibited a specific and areal capacitance of 93F/g and 466 mF/cm 2, respectively and showed an outstanding cycling stability after 10000 cycles. Graphical abstract: Image 1 Highlights: Polypyrrole nanospheres are assembled on the surface of PMo12-x Wx modified MWNT. PMo12-x Wx as well as –COOH bearing on MWNTs endow PPy with high doping level. MPN10 electrode can provide a high specific capacitance of 570 F/g. The symmetric supercapacitor shows an areal capacitance of 466 mF/cm 2 .